2011
DOI: 10.1111/j.1745-7599.2011.00597.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Tai Chi exercise on coronary heart disease: A systematic review

Abstract: Nurse practitioners (NPs) are in an ideal position to facilitate health promotion and disease prevention. NPs may prescribe Tai Chi as an alternative exercise therapy for their patients who are at risk for developing CHD and even for those with existing CHD. Tai Chi exercise may help prevent and even reverse the progression of cardiac disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…It has become an effective mean of secondary prevention of CVDs. It is found that Tai Chi could not only contribute to lowing BP smoothly, recovering the heart function, reversing cardiovascular risk factors, but also improving symptoms and quality of life (QOL) [5557]. Although there are 2 SRs about Tai Chi on lowering resting blood pressure (including hypertension, acute myocardial infarction, older people with chronic conditions, healthy elderly men, middle-aged women, and other diseases) [52, 57], the role of Tai Chi for EH is still unknown due to different inclusion criteria and search strategies.…”
Section: Discussionmentioning
confidence: 99%
“…It has become an effective mean of secondary prevention of CVDs. It is found that Tai Chi could not only contribute to lowing BP smoothly, recovering the heart function, reversing cardiovascular risk factors, but also improving symptoms and quality of life (QOL) [5557]. Although there are 2 SRs about Tai Chi on lowering resting blood pressure (including hypertension, acute myocardial infarction, older people with chronic conditions, healthy elderly men, middle-aged women, and other diseases) [52, 57], the role of Tai Chi for EH is still unknown due to different inclusion criteria and search strategies.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the Dietary Approaches to Stop Hypertension (DASH) diet can decrease CHD risk among women 25 and decrease LDL-C. 19 T'ai chi (TC) exercise can improve traditional blood lipids [26][27][28] and is ideal for older adults. 28 However, research on the additive effect of TC to DASH diet education on traditional and emerging risk factors, such as apo B and LDL particle size, is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Tai Chi enhances aerobic capacity, immune function, and endothelial function (Frishman et al, 2009). Furthermore, Tai Chi exercise reduces CHD and stroke risks by benefiting the lowering of blood pressure and possibly lipid modification (Dalusung-Angosta, 2011).…”
Section: Introductionmentioning
confidence: 99%